Methodologies and models for information audit. Reflexive analysis - González Guitián, María Virginia; Ponjuán Dante, Gloria (Revista General de Información y Documentación, 2014)
A full walkthrough in reference of the theoretical and methodological aspects of the information audit is made, from which the most common aspects are analyzed in each one of the 13 methodologies and models reported in the world wide literature. Comparisons between these methodologies and models are established under a reflexive point of view that consider these frameworks as main important tools for diagnosing the state of the information management systems and the information policies in the modern organizations. It was determined that the most significant frameworks to this matter are the models of Villardefrancos-Álvarez, and that of Orna, and methodologies to Soy i Aumatell, Buchanan & Gibb, Henczel and González-Guitián. A tendency to perform information audit using hybrid frameworks is closely observed. Finally some important considerations are explored, where the importance of the subject is exposed and the opinion of the author is given.
Keywords: Information Audit; Information Management; Methodologies; Models.